γ-Cyclodextrin hydrogel for the sustained release of josamycin for potential ocular application - Jennifer Huling; Stefan Oschatz; Helge Lange; Katharina Anna Sterenczak; Thomas Stahnke; Jana Markhoff; Oliver Stachs; Steffen Möller; Nasrullah Undre; Anita Peil; Anselm Jünemann; Niels Grabow; et al. (Taylor & Francis Group, 2024)
Glaucoma is the leading cause of blindness worldwide. However, its surgical treatment, in particular via trabeculectomy, can be complicated by fibrosis. In current clinical practice, application of the drug, Mitomycin C, prevents or delays fibrosis, but can lead to additional side effects, such as bleb leakage and hypotony. Previous in silico drug screening and in vitro testing has identified the known antibiotic, josamycin, as a possible alternative antifibrotic medication with potentially fewer side effects. However, a suitable ocular delivery mechanism for the hydrophobic drug to the surgical site does not yet exist. Therefore, the focus of this paper is the development of an implantable drug delivery system for sustained delivery of josamycin after glaucoma surgery based on crosslinked γ-cyclodextrin. γ-Cyclodextrin is a commonly used solubilizer which was shown to complex with josamycin, drastically increasing the drug's solubility in aqueous solutions. A simple γ-cyclodextrin crosslinking method produced biocompatible hydrogels well-suited for implantation. The crosslinked γ − cyclodextrin retained the ability to form complexes with josamycin, resulting in a 4-fold higher drug loading efficiency when compared to linear dextran hydrogels, and prolonged drug release over 4 days.